1989
DOI: 10.1139/z89-346
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring heart rate and body temperature in red foxes (Vulpes vulpes)

Abstract: KREEGER, T. J., MONSON, D., KUECHLE, V. B., SEAL, U. S., and Tester, J. R. 1989. Monitoring heart rate and body temperature in red foxes (Vulpes vulpes). Can. J. Zoo!. 67: 2455 -2458. Twenty-four captive-raised red foxes were surgically implanted with radios that transmitted both heart rate and body temperature. Successive fox pairs were placed in a 4.1-ha observation pen for 2 weeks and behavior was video recorded. The radio signal was recorded on the audio portion of the video tape for computer decoding. Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…The observational methods used in this study demonstrate that many behavioral responses of mountain sheep and desert mule deer to jet aircraft noise are subtle and differ with experience, age, and season (Jacobsen and Stuart 1978, Moen 1978, Kreeger et al 1989.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The observational methods used in this study demonstrate that many behavioral responses of mountain sheep and desert mule deer to jet aircraft noise are subtle and differ with experience, age, and season (Jacobsen and Stuart 1978, Moen 1978, Kreeger et al 1989.…”
Section: )mentioning
confidence: 99%
“…A radio frequency pulse was transmitted for each depolarization of the ventricles detected (Kreeger et al 1989), so that the biologist received a signal similar to a tracking signal (Pauley et al 1979) transmitted by radio collars.…”
mentioning
confidence: 99%
“…Researchers have used this tool extensively to monitor activity patterns, to determine home range size, and to measure physiological parameters (Amlaner andMacDonald 1980, White andGarrott 1990). Continual monitoring of activity patterns and physiological parameters is often possible in a controlled laboratory or enclosure setting (see Kreeger et al 1989, Canguilhem et al 1994, Cats et al 1995, Lefcourt and Adams 1996, Buuse and Malpas 1997). Some researchers have been able to rely on radiotelemetry to collect continuous data from free-ranging animals (Cooper andCharles-Dominique 1985, Scheibe et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have been conducted on the hunting of red deer using dogs (Bateson and Bradshaw , Harris et al ), there have been few objective reports of the activity of hunting foxes using dogs. Although one study reported heart rate and temperature responses of captive foxes to being chased by dogs, these data likely have little direct relevance to the pursuit of wild foxes by foxhounds (Kreeger et al ); several other studies have commented on aspects of hunting foxes with dogs, although these have relied principally on responses to questionnaires (McDonald and Johnson , Heydon and Reynolds , Baker et al ) or indirect indices of fox numbers (Baker et al , Baker and Harris ). Although there has been reference made to the practice, as far as we are aware, there has been no prior detailed description of the activity of dogs used to flush foxes to guns (Burns et al , Heydon and Reynolds ).…”
mentioning
confidence: 99%